Radiological assessment of urban soil samples in the residents of a central Anatolian volcanic province, Turkey - Turhan, Şeref (Informa UK Limited, 2022)
The concentration of natural and anthropogenic radionuclides, emanation fraction (EF), and mass (χM) and area (χA) exhalation rate of 222Rn in urban soil samples collected from dwelling areas in Nevşehir city located in a region known as the central Anatolian volcanic province of Turkey were determined using gamma-ray spectroscopy. The average activity concentrations of 226Ra, 228Ra, 40K and 137Cs were measured as 60.2 ± 3.8, 50.1 ± 2.8, 631.0 ± 29.7 and 5.5 ± 0.4 Bq/kg, respectively. The average concentration of 222Rn in soil and air was estimated as 27 kBq/m3 and 84 Bq/m3, respectively. The average values of EF, χM and χA were found as 20%, 25.4 μBq/kg⋅s and 20.2 mBq/m2⋅s, respectively. The average values of outdoor absorbed gamma dose rate, external and internal annual effective dose and lifetime cancer risk estimated for radiological assessment were found as 85 nGy/h, 104 µSv/y, 797 µSv/y and 4.1 × 10-4, respectively.
Keywords: Soil; Turkey; Radiation Monitoring; 13. Climate action; 11. Sustainability